2002
DOI: 10.1038/oby.2002.169
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal Obesity and Ethnic Differences in Diabetes Awareness, Treatment, and Glycemic Control

Abstract: OKOSUN, IKE S. AND G.E. ALAN DEVER. Abdominal obesity and ethnic differences in diabetes awareness, treatment, and glycemic control. Obes Res. 2002;10: 1241-1250. Objective: To compare racial/ethnic differences in diabetes awareness, treatment, and glycemic control between non-Hispanic white, non-Hispanic black, and Hispanic Americans. We also determined the impact of abdominal obesity on racial/ethnic differences in diabetes awareness, treatment, and glycemic control between these population groups. Research… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
23
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 39 publications
5
23
0
1
Order By: Relevance
“…Similar to our results, previous studies have shown a positive association between glycemic control and adiposity (39,42,43) and cholesterol levels (21,44). Studies in individuals without diabetes have also shown similar correlations between lipids and A1C (45)(46)(47)(48).…”
Section: Multivariable Analysessupporting
confidence: 81%
“…Similar to our results, previous studies have shown a positive association between glycemic control and adiposity (39,42,43) and cholesterol levels (21,44). Studies in individuals without diabetes have also shown similar correlations between lipids and A1C (45)(46)(47)(48).…”
Section: Multivariable Analysessupporting
confidence: 81%
“…6 Also there are several studies proved that level of awareness depends on socioeconomic gradient, culture and ethnic variation. [7][8][9] The results of the present study were similar to the findings of study conducted on knowledge on risk factors of diabetes in a different population. 10 The majority of study respondents agreed that sugar level in uncontrolled diabetes mellitus will be high and accurate method of checking sugar is through blood investigations.…”
supporting
confidence: 81%
“…Racial-ethnic differences in the relationship between BMI, percent body fat, and body-fat distribution among whites, Hispanics, and African Americans also have been reported and may contribute to the sex and ethnic variations in NAFLD prevalence. 41,42 Although waist circumference was not measured in our study, persons with an increased waist circumference have been shown to be more likely to exhibit type 2 diabetes, dyslipidemia, and other components of metabolic X syndrome than persons with a normal waist circumference independent of race, BMI, age, income, socioeconomic class, or physical activity. 43 Although waist-to-hip ratio generally is thought to correlate with visceral adiposity, Conway et al 44 have shown that waist-to-hip ratio correlates with visceral adiposity in white women but not in African-American women, again highlighting the existence of racial variability in these anthropometric parameters.…”
Section: Discussionmentioning
confidence: 85%